NUMERICAL MODELING OF LONG SHORE TRANSPORT RATE IN COASTAL STRUCTURE PLANNING - Koko Ondara; Hadhrat Khalil (Jurnal Kelautan, 2019)
Demak Regency is one of the regencies in the coastal region north of Central Java, which has a abrasion. The coastal area of Surodadi, Sayung Subdistrict, Demak Regency is one of the areas that experienced severe abrasion. The purpose of this study is to analyze the coastal dynamics that occur and design appropriate conservation and rehabilitation systems to reduce the impact of abrasion and coastal protection. This study uses primary data carried out at 2016. The analyzes carried out were wind, wave, tidal analysis, shoreline changes and analysis of recommendation structures. The protection scenorio plan uses two alternative structures namely breakwater and seawall. Analysis using a breakwater indicates that the results of sedimentation due to the structure are unsatisfactory. After 10 years, the breakwater produces ± 100 m sedimentation from the initial coastline. The modeling results show that the seawall can prevent further abrasion in the study site even if it does not cause sedimentation (except on the coastline that juts into the mainland).